1990
DOI: 10.1139/z90-025
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal serum glucose, progesterone, and Cortisol levels of black bears (Ursus americanus)

Abstract: Sixty-two black bears were captured at different seasons during the years 1983–1987. Bears were anesthetized in their dens during the winter and parts of the fall and spring, while bears captured during the summer were snared prior to anesthesia. Radioimmunoassays for both Cortisol and progesterone were validated on black bear serum. An improved, rapid progesterone radioimmunoassay for black bear serum is reported. Serum glucose demonstrated a tendency for reduction during spring. Serum progesterone levels did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 19 publications
5
28
1
1
Order By: Relevance
“…Thus, further investigations are needed to explain the apparent interpopulation difference in E 2 between female polar bears from Svalbard and Canada. The cortisol concentrations in this study showed large variations between individuals, and the cortisol levels were higher than those reported for female black bears caught in foot snares during spring (March-May) (Harlow et al 1990). The concentrations may be elevated as a consequence of immobilization and handling, but there seemed to be no differential effect of handling between reproductive groups.…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Thus, further investigations are needed to explain the apparent interpopulation difference in E 2 between female polar bears from Svalbard and Canada. The cortisol concentrations in this study showed large variations between individuals, and the cortisol levels were higher than those reported for female black bears caught in foot snares during spring (March-May) (Harlow et al 1990). The concentrations may be elevated as a consequence of immobilization and handling, but there seemed to be no differential effect of handling between reproductive groups.…”
Section: Discussioncontrasting
confidence: 67%
“…The independent variables were capture date (Julian date), age (years, months), body mass (kilograms), ΣPCBs (nanograms per gram lipid weight), and PCB-118 (nanograms per gram lipid weight). Effects on plasma P 4 concentrations due to stress of handling were also examined, because stress-related cortisol production may lead to higher blood levels of adrenal P 4 (Harlow et al 1990;Plotka et al 1983). …”
Section: Polychlorinated Biphenyls and Reproductive Hormones In Femalmentioning
confidence: 99%
“…None of the polar bears had extremely high levels of cortisol, and the individual variation may have been related to differences in chase time, but unfortunately, individual chase time was not recorded in this study. Cortisol levels were higher in black bears in winter than in summer, and generally higher than found for polar bears (Harlow et al, 1990). It is uncertain whether this difference in cortisol levels is due to less capture stress among polar bears or species variability.…”
Section: Discussionmentioning
confidence: 84%
“…Upon entrance into Phase III, corticosterone levels in laboratory rats had risen by 19-fold (100). Overwintering black bears likewise experience increases in circulating cortisol; however, winter dormant raccoon dogs experienced a decline in plasma cortisol suggesting that they may use an alternative axis to stimulate lipolysis (246,391).…”
Section: Glucocorticoidsmentioning
confidence: 99%